What Do City Planners Need to Know? - Saghir, Chade; Sands, Gary; Wambu, Charles (My University, 2015)
Do university planning programs provide their graduates with the knowledge, skills and values they will require in their professional careers? A national on-line survey of planning practitioners finds that there is a close correspondence between what planners consider to be important and the curriculum standards and criteria of the Planning Accreditation Board, which are the model for the curricula of accredited Planning degrees. Individual elements are ranked high in importance, regardless of respondents’ educational and occupational characteristics. Both Globalization and Sustainability/Environmental Quality received relatively low importance rankings from respondents; this suggests areas for increased attention by universities and continuing education
Keywords: urban planning education; urban planning curriculum; professional planning competencies; planning Accreditation Board